Strengthening Students' Attitudes of Tolerance Through Diversity-Based Civic Education in Elementary Schools - Syarif, Ahmad; Trirahmayati, Tiara; Dani, Putri Rahma; Zulhidah, Zulhidah (Ahlussunnah: Journal of Islamic Education, 2025)
Civic education plays a strategic role in shaping students' character, especially in terms of tolerance as a manifestation of diversity values since elementary school. The challenges of social diversity, the spread of digital information that often gives rise to stereotypes, and the tendency for intolerant attitudes to emerge at an early age make it necessary to systematically internalize tolerance education through the learning process at school. This study aims to describe how students' attitudes of tolerance are strengthened through diversity-based Civic Education in Islamic Elementary Schools. The research used a descriptive qualitative method with data collection techniques through observation of learning activities, interviews with teachers and students, and documentation of learning tools. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing with validation through triangulation of techniques and sources. The results of the study show that teachers integrate diversity values through group discussions, inspirational stories of national figures, collaborative games, and social habits in classroom interactions. Students' tolerance attitudes are demonstrated through behaviors such as respecting opinions, accepting differences, and the ability to work together in heterogeneous groups. However, time constraints and variations in methods pose obstacles to implementation. This study concludes that tolerance can be strengthened optimally if citizenship education is designed to be experience-based, collaborative, and contextual to students' lives.